Production potential and mapping of medicinal and aromatic plants in the Azilal forest (central High Atlas of Morocco) - Sakanya, Esnart Stephanie; Lahssini, Said; Khattabi, Abdellatif; Pruneau, Diane; Diarra, Saliha (Ethnobotany Research and Applications, 2026)
Background: In Morocco, a Mediterranean biodiversity hotspot, medicinal and aromatic plants (MAPs) play a key socioeconomic and cultural role, particularly in traditional healthcare and rural livelihoods. Yet, increasing anthropogenic and climatic pressures threaten their sustainability, especially in mountainous forest ecosystems where quantitative data on species distribution and productivity remain scarce. Methods: To address this gap, a phytoecological inventory was conducted in the Azilal forest using a stratified random sampling design across nineteen plots of 400 m² each, along with aboveground phytomass assessment of dominant MAP species to assess floristic diversity and production potential. Results: A total of 40 MAP species belonging to 22 botanical families were recorded, with Asteraceae, Fabaceae, and Lamiaceae being the most represented. Three distinct floristic facies were identified, reflecting pronounced spatial heterogeneity and areas of ecological fragility. Phytomass estimates showed substantial interspecific variability, with fresh biomass ranging from 66.84 to 998.94 kg·ha⁻¹ and dry biomass from 4.73 to 430 kg·ha⁻¹. High production potential was observed in a limited number of species, notably Chamaerops humilis L., Cistus laurifolius L.., and Asphodelus ramosus L., whereas approximately 80% of the recorded species exhibited low cover rate and limited biomass, indicating high vulnerability to disturbance and overharvesting. Conclusions: This study provides the first quantitative and spatially explicit evaluation of MAPs diversity and productivity in the Azilal forest. The resulting phytomass estimates and ecological facies mapping provide practical tools for identifying high-potential economic zones and prioritizing conservation areas, thereby supporting adaptive management strategies that balance local development and ecosystem preservation. Keywords: medicinal and aromatic plants (MAPs), Azilal forest, non-timber forest products (NTFP), inventory, biomass production, sustainable management, conservation, Morocco